Ambiances commemoratives : concepts, méthodologies, implications - Shanti Sumartojo (L'Espace Politique)
The author argues that commemoration is more complicated than simply “connecting” people to the past, promulgating particular political agendas or reinforcing collective rituals of national identity. Instead, she proposes that the we need to approach it from how it is felt and experienced, rather than focus only its history, discourse or symbolism. She advocates for an approach to commemoration that focuses on atmospheres, conceptually and empirically. In this paper, she suggests the use of methodologies that, by attending to atmospheres, consider how people feel in and about commemorative sites. She shows how digital, sensory and/or visual ethnographic approaches can be used, and explains how these are helping to extend understandings of commemorative spacetimes. Finally, she considers two areas of possibility offered her approach. If such moves can make possible new understandings of commemorative sites and events in peoples’ lives, it is because they help illuminate the relationship between individual and collective experience, identifying how shared affects can amplify events and make them more meaningful, but also how feelings can be subverting or loosening our connection to state narratives. Attending to the experiential alongside the discursive, in other words, helps us understand both the durability and the fragility of shared identity narratives.